PENERAPAN STANDARD OPERATIONAL PROCEDURE LAUNDRY SUPERVISOR PADA DEPARTMENT HOUSEKEEPING HOTEL NOVOTEL PEKANBARU - Nurul Huda; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Novotel Hotel Pekanbaru is a 4 star hotel (****) and belongs to the type of city hotel under the auspices of the management of ACCOR Hotels. Hotel Novotel Pekanbaru already has Standard Operating Procedures (SOP) that have been made by the central management namely ACCOR, SOP laundry supervisor is very important for the smooth work of a supervisor. This research uses descriptive qualitative method to analyze problems based on interview, observation and documentation data collection techniques which are then drawn conclusions. The subject of this study amounted to 3 people, the purpose of this study was to find out how to apply the standard operational procedures of the supervisor's laundry and the efforts made by the hotel in carrying out SOP to the laundry supervisors of the Novotel Pekanbaru Hotel. The results of this study show that the implementation of the standard operation procedure for laundry supervisors at the housekeeping department of the Novotel Pekanbaru Hotel has been carried out in accordance with the Standard Operating Procedures that have been set. Keywords : SOP, Laundry, Supervisor